Public-private partnership as a tool for innovative development of urban areas - S.V. Svirko; T.O. Vlasiuk; O.A. Shevchuk; I.V. Suprunova (Економіка, управління та адміністрування)
The article deals with the issue of public-private partnership as a tool for innovative development of urban areas. The state of public-private partnership in Ukraine was analyzed and a conclusion was made about the emphasis of the latter on the urban economy. In the process of considering urbanized territories as complex systems, a model of public-private partnership development in urbanized territories was formed. In order to implement the specified model, the implementation mechanism of public-private partnership in the field of innovative development of urban areas has been improved. The goal is identified, which is to ensure long-term cooperation between the state and the private sector by pooling resources to increase the level of innovative activity, the tasks and principles of implementation of public-private partnership in the field of innovative development are defined. The implementation algorithm and powers of public-private partnership subjects were studied, in particular, it was proposed to improve the institutional model in terms of the functions and powers of the subjects of state regulation of public-private partnership in the field of innovative development.